(untitled) (Stamford Journal of Microbiology, 2017)
Strawberry is a popular fruit item consumed by people all over the world for its exceptional flavor and aroma. This fruit is being used to prepare a wide range of food items. Strawberries when consumed by people without undergoing any processing, the condition may not be good enough. People may get sick after consuming raw strawberries. Our current study identified several pathogenic bacteria which are very known in causing health related problems. E. coli was found in one sample (1.0×102 cfu/g), Staphylococcus aureus was commonly present in all of the five samples (up to 1.2×106 cfu/g), Klebsiella spp. was found to be present in two samples (within 1.0×103 cfu/g) and Pseudomonas spp. was present in three samples (8.2×104 cfu/g), respectively. All isolated bacteria showed some degree of drug resistant traits against some commonly used antibiotics. The most important and promising part of the study was to successfully find the antimicrobial activity of strawberries against seven types of pathogenic bacteria Stamford Journal of Microbiology, Vol.6(1) 2016: 16-19